Tendon Morphology and Mechanical Properties Are Associated With the Recovery of Symptoms and Function in Patients With Achilles Tendinopathy - Corrigan, Patrick (Orthop J Sports Med, 2020)
BACKGROUND: Achilles tendinopathy is a debilitating overuse injury characterized by pain, altered Achilles tendon structure, and impaired functional performance. Evaluating tendon structure as part of the physical examination may help establish a well-defined prognosis. However, the usefulness of measuring tendon structure for developing a prognosis has been questioned since structural abnormalities can exist without symptoms. PURPOSE: To determine whether initial measures of tendon morphology and mechanical properties were associated with patient-reported symptoms and calf muscle endurance at baseline, 6-month follow-up, and 1-year follow-up by prospectively following a cohort of individuals with Achilles tendinopathy. STUDY DESIGN: Cohort study; Level of evidence, 2. METHODS: A total of 59 participants with midportion or insertional Achilles tendinopathy completed an initial assessment and follow-up assessments at 6 months and 1 year. At the initial assessment, patient-reported symptoms, calf muscle endurance, and Achilles tendon thickening were evaluated, and Achilles tendon mechanical properties were estimated. At the 6-month and 1-year follow-up assessments, patient-reported symptoms and calf muscle endurance were reevaluated. RESULTS: Greater Achilles tendon thickening at the initial assessment was consistently associated with worse patient-reported symptoms and calf muscle endurance at each assessment. Changes in symptoms over the year were moderated by the initial shear modulus of the tendon, with a lower shear modulus associated with less improvement in symptoms. Lower viscosity at the initial assessment was also associated with worse calf muscle endurance at each assessment. CONCLUSION: Measures of tendon morphology and mechanical properties appear to be associated with patient-reported symptoms and calf muscle function for patients with Achilles tendinopathy.